PHYSICOCHEMICAL CHARACTERISTICS OF THE SOIL IN SACCHARUM OFFICINARUM L. (SUGAR CANE) CULTIVATION IN THE PROVINCE OF PASTAZA, ECUADORIAN AMAZON - González Víctor, Jaque Darwin, Salazar-Álvarez Edgar; Andrade-Yucailla Verónica, Hidalgo-Guerrero Irene, Saltos-Espín Rubén (Chelonian Research Foundation, 2024)
The Ecuadorian Amazon is a mega-diverse ecological niche in flora and fauna. Currently, crop areas that serve as a source of sustenance for rural populations have increased. It was essential to evaluate the physicochemical characteristics of the soil in sugarcane crops (Saccharum officinarum L.) in the Pastaza province of the Ecuadorian Amazon to evaluate its fertility in comparison to a primary forest (PF). The composite soil samples were collected in five agricultural production units (APUs) and PF as a comparison agent at a depth of 0.15 m. The physicochemical variables evaluated were: bulk density, texture, pH, organic matter, macronutrients, micronutrients, and base ratio. High concentrations of organic matter were found (11.99 to 12.78%), as well ashighly acidic soils (pH 3.90 to 4.67) and sandy loam and silty soil textures. Macronutrients were generally medium to low in concentration, and micronutrients medium to high. 64.70% of the variables are concentrated in CP1 and CP2; as factors with the greatest contribution to soil fertility, they are affected by P, NH4, clay, B, S, Mn, Fe, silt, sand, Mg, Zn, sum of bases, Ca, K, and Cu. The physicochemical results of the soil with S. officinarum and PF cultivation demonstrated a characteristic behavior of Amazonian soils. S. officinarum did not exert any influence on soil fertility, and it adapted fully to the nutritional and highly acidic conditions of the Amazonian soils. Keywords:Macronutrients, micronutrients, soil texture, principal component.